2018
DOI: 10.1159/000494580
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Management in a Nephrology Service: Lessons Learned from Hurricane Maria

Abstract: Background: Puerto Rico suffered a major humanitarian ­crisis after Hurricane Maria. We describe our experience with patients with renal disease in an academic medical center. Summary: A comprehensive emergency response plan should be developed, shared and discussed with the team and the patients prior to the hurricane. The needs of the staff should not be ignored to ensure their ability to participate as responders. Physical damage to facilities, lack of basic services, shortage of disposable products, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…55 It is notable that 1 year after the hurricane 3 of the 52 dialysis units on Puerto Rico still are closed. 56 In the same article, Bonilla-Felix and Suarez-Rivera 56 reported their experience in Puerto Rico, adding a number of highly interesting recommendations for better preparedness for the future.…”
Section: Patients On Maintenance Hemodialysismentioning
confidence: 99%
See 1 more Smart Citation
“…55 It is notable that 1 year after the hurricane 3 of the 52 dialysis units on Puerto Rico still are closed. 56 In the same article, Bonilla-Felix and Suarez-Rivera 56 reported their experience in Puerto Rico, adding a number of highly interesting recommendations for better preparedness for the future.…”
Section: Patients On Maintenance Hemodialysismentioning
confidence: 99%
“…55 A more recent study reported by the Milken Institute of Public Health at The George Washington University estimated a total excess mortality of 2,975, similar to the death toll reported after the terrorist attack at the World Trade Center on September 11, 2001. 56 This makes Hurricane Maria the worst natural catastrophe in Puerto Rico in the past century and, after the 1900 Galveston hurricane, the second deadliest hurricane in US history, with a higher death toll than Hurricane Katrina.…”
Section: Patients On Maintenance Hemodialysismentioning
confidence: 99%
“…Deadly hurricane Maria devastated in 2017 most of Puerto Rico next to Dominica and the US Virgin Islands, making communication, transport and provision of water and fuel almost impossible for most of the affected area [75], impeding dialysis provision [75,76], and causing many patients to move elsewhere, especially to Florida [76].…”
Section: Other Natural Disasters Than Earthquakesmentioning
confidence: 99%
“…7 The emergency preparedness and response literature is growing and reflects an expanding interest in and evolution of the science of hospital preparedness. [8][9][10][11][12][13][14][15][16][17] Although there are general themes described in the literature from specific hospitals that have experienced disasters that disrupted normal operations and patient care, [18][19][20][21][22][23][24][25][26][27][28] and although there is literature describing how hospitals should prepare for and respond to internal and external disasters, to the best of our knowledge there are no structured reviews on this topic. The objective of this paper is to provide a structured, detailed review and description of the common themes and lessons from disaster events that directly affect hospitals and health systems via damage to physical infrastructure or degradation of resources, thereby disrupting the basic function of patient care.…”
Section: Introductionmentioning
confidence: 99%